Gene Expression and DNA Methylation Status of Glutathione S-Transferase Mu1 and Mu5 in Urothelial Carcinoma. - Shou-Chieh Wang (PLoS ONE, 2016)
Bladder cancer is highly recurrent after therapy, which has an enormous impact on the health and financial condition of the patient. It is worth developing diagnostic tools for bladder cancer. In our previous study, we found that the bladder carcinogen BBN increased urothelial global DNA CpG methylation and decreased GSTM1 protein expression in mice. Here, the correlation of BBN-decreased GSTM1 and GSTM gene CpG methylation status was analyzed in mice bladders. BBN treatment decreased the protein and mRNA expression of GSTM1, and the CpG methylation ratio of GSTM1 gene promoter was slightly increased in mice bladders. Unlike mouse GSTM1, the human GSTM1 gene tends to be deleted in bladder cancers. Among 7 human bladder cancer cell lines, GSTM1 gene is really null in 6 cell lines except one, T24 cells. The CpG methylation level of GSTM1 was 9.9% and 5-aza-dC did not significantly increase GSTM1 protein and mRNA expression in T24 cells; however, the GSTM5 gene was CpG hypermethylated (65.4%) and 5-aza-dC also did not affect the methylation ratio and mRNA expression. However, in other cell lines without GSTM1, 5-aza-dC increased GSTM5 expression and decreased its CpG DNA methylation ratio from 84.6% to 61.5% in 5637, and from 97.4% to 75% in J82 cells. In summary, two biomarkers of bladder tumor were provided. One is the GSTM1 gene which is down-regulated in mice bladder carcinogenesis and is usually deleted in human urothelial carcinoma, while the other is the GSTM5 gene, which is inactivated by DNA CpG methylation.